2019
DOI: 10.2147/phmt.s188014
|View full text |Cite
|
Sign up to set email alerts
|

<p>Prune belly syndrome: current perspectives</p>

Abstract: Prune belly syndrome (PBS) is a rare but morbid congenital disease, classically defined by a triad of cardinal features that includes cryptorchidism, urinary tract dilation and laxity of the abdominal wall musculature. Children often require numerous surgical interventions including bilateral orchidopexy as well as individually tailored urinary tract and abdominal wall reconstruction. Along with the classic features, patients with PBS often experience gastrointestinal, orthopedic, and cardiopulmonary comorbidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
42
0
14

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(62 citation statements)
references
References 68 publications
(55 reference statements)
1
42
0
14
Order By: Relevance
“…Patient past medical history, family history and his mother's pregnancy history did not contribute to diagnosis BACKGROUND P rune Belly Syndrome (PBS) is a rare congenital disorder characterized by a triad of deficient abdominal wall muscles, cryptorchidism and urinary tract anomalies (including hydroureteronephrosis). The syndrome affects 3.8 per 100,000 live male births [1][2][3][4] . Over 95% of patients are boys 5 .…”
Section: Ethical Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patient past medical history, family history and his mother's pregnancy history did not contribute to diagnosis BACKGROUND P rune Belly Syndrome (PBS) is a rare congenital disorder characterized by a triad of deficient abdominal wall muscles, cryptorchidism and urinary tract anomalies (including hydroureteronephrosis). The syndrome affects 3.8 per 100,000 live male births [1][2][3][4] . Over 95% of patients are boys 5 .…”
Section: Ethical Considerationsmentioning
confidence: 99%
“…Some studies have suggested that the abdominal muscle deficiency is due to foetal abdominal distension of different causes including urethral obstruction with enlarged bladder and hydronephrosis. Also mesenchymal developmental defects have been suggested as the underlying defect 1 . The cause of PBS is unknown 6 .…”
Section: Ethical Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Існує гіпотеза, що розширена сечо видільна система або облітерація пахових каналів ускладнюють нормальне опускання яєчок або вони можуть бути прикріплені до сечоводу. Однак крипторхізм не спостеріга ється у дітей із розширеним сечовим міхуром іншої етіології [2,15,25].…”
unclassified
“…Клініка Читайте нас на сайті: http://med expert.com.ua Гаррісона) може бути у багатьох дітей із син дромом Пруне-Беллі. Також може спостері гатися звуження грудної клітки у поперечно му напрямку (килевидна деформація грудної клітки) [2,25].…”
unclassified